PERAN KADER KESEHATAN JIWA DALAM MELAKUKAN PENANGANAN GANGGUAN JIWA - Dwi Indah Iswanti; Sri Puji Lestari (Jurnal Ilmu Keperawatan Jiwa, 2018)
THE ROLE OF MENTAL HEALTH CADRES IN THE HANDLING OF MENTAL PATIENTS ABSTRACTMental disorder is a manifestation of the form of behavioral aberrations due to emotional distortion to the point that there is an irregularity in behavior. This happens because of the decline in all psychological functions. According to World Health Organization data of 35 million people affected by depression, 60 million people exposed to bipolar, 47.5 million exposed to dementia and 21 million exposed to schizophrenia. Exploration study on the role of mental health cadres in the handling of mental patients in RW 06 Kelurahan Gemah Semarang City. The research method used qualitative research with phenomenology approach. Participants in this study is 3 (three) of mental health cadres. The roles of mental health cadres for health counseling in RW 06 Kelurahan Gemah Semarang City by collecting data on people with mental disorders, recording individuals with mental disorders, getting approval from families to obtain information and carry out monitoring the development of individuals with mental disorders. TAK and rehabilitation activities require a strategic approach by following procedures in the implementation of TAK, Providing information to mobilize families to conduct referrals in patients with mental disorders and recording and documenting the development of mental health in the available observation sheets. Keywords: Roles; Mental Health Cadres; Patient Handling